Gait Pattern Differences Among Children With Bilateral Cerebral Palsy - Domagalska–Szopa, Małgorzata; Szopa, Andrzej (Frontiers in Neurology, 2019)
Background: Recently, promising study findings have revealed different gait patterns corresponding with postural patterns in children with unilateral cerebral palsy (CP). Therefore, the objective of this study was to evaluate whether different gait patterns corresponding to postural patterns in children with bilateral CP could be statistically significant according to a cluster analysis. Methods: 58 participants with bilateral CP and 45 matched children with normal growth and development. The participants walked barefoot along a treadmill at their own pace. Three-dimensional kinematic data were collected using the Measuring System for Motion Analysis. To characterize gait patterns, the GGI and its 16 distinct gait parameters were used. The participants were divided into 4 subgroups according to their postural patterns. Results: A cluster analysis revealed 4 gait patterns corresponding to postural patterns: 1) normal gait pattern corresponded to neutral posture; 2) balanced gait pattern corresponded to balanced posture; 3) lordotic gait pattern corresponded to lordotic postural pattern; 4) swayback gait pattern corresponded to backward-leaning posture. There were significant differences in mean GGI and various clusters in the 8 GGI gait parameters: cadence, mean pelvic tilt; mean pelvic rotation, minimum hip flexion, peak hip abduction in swing; knee flexion at initial contact, and peak dorsiflexion in stance. Conclusion: Our results showed that gait discrepancies among children with bilateral CP were not simply a result of lower limb kinematic deviations in the sagittal plane. Information on different gait patterns could improve early therapy in children with bilateral CP before abnormal gait patterns are fully established.